Innovation in retail marketing: sensory experience and its influence on women's footwear purchase decisions - Zamudio Norabuena, Leonardo Alonso; Castillo Cueva, Milagros Johana; Morales-Alonso, Gustavo; Navarro-Castillo, Yulissa Maruschka (Papeles de Europa, 2025)
The main objective of this study was to identify the predominant elements influencing the purchasing decision-making process in a footwear retail setting, considering physical product attributes (design, color, price, and brand), the commercial environment (lighting and music), and customer service (quality of service provided). A quantitative, descriptive-level approach was employed, using cross-sectional data analysis. Data were collected through a survey administered to 59 randomly selected women, all aged 35 or older, who had made purchases at the store. The information was processed using descriptive statistics. The main findings indicated that 56% of respondents prioritized footwear design, while environmental and service-related elements such as lighting (84%), music (75%), and customer service (81%) significantly contributed to the decision-making process. The study confirmed that additional experiential elements related to customer service play a pivotal role in shaping purchasing decisions, with design emerging as the most salient factor when selecting footwear.
Keywords: footwear market; store atmosphere; sensory stimuli; female costumer; customer service